A real‐time applicator position monitoring system for gynecologic intracavitary brachytherapy. Issue 1 (12th December 2013) - Xia, Junyi; Waldron, Timothy; Kim, Yusung
Abstract : Purpose: : To develop a real‐time applicator position monitoring system (RAPS) for intracavitary brachytherapy using an infrared camera and reflective markers. Methods: : 3D image‐guided brachytherapy requires high accuracy of applicator localization; however, applicator displacement can happen during patient transfer for imaging and treatment delivery. No continuous applicator position monitoring system is currently available. The RAPS system was developed for real‐time applicator position monitoring without additional radiation dose to patients. It includes an infrared camera, reflective markers, an infrared illuminator, and image processing software. After reflective markers are firmly attached to the applicator and the patient body, applicator displacement can be measured by computing the relative change in distance between the markers. The reflective markers are magnetic resonance imaging (MRI) compatible, which is suitable for MRI‐guided HDR brachytherapy paradigm. In our prototype, a Microsoft Kinect sensor with a resolution of 640 by 480 pixels is used as an infrared camera. A phantom study was carried out to compare RAPS' measurements with known displacements ranging from −15 to +15 mm. A reproducibility test was also conducted. Results: : The RAPS can achieve 4 frames/s using a laptop with Intel ® Core™2 Duo processor. When the pixel size is 0.95 mm, the difference between RAPS' measurements and known shift values varied from 0 to 0.8 mm with the mean value of 0.1 mm and a standard deviation of 0.44 mm. The system reproducibility was within 0.6 mm after ten reposition trials. Conclusions: : This work demonstrates the feasibility of a real‐time infrared camera based gynecologic intracavitary brachytherapy applicator monitoring system. Less than 1 mm accuracy is achieved when using an off‐the‐shelf infrared camera.